Exit exams and curriculum design in Higher Education: A systematic review - Teshome, Samson Worku (Journal of Education Policy and Management Studies, 2025)
As a standard for evaluating students' preparedness for graduation and professional practice, exit exams have emerged as a crucial element of higher education.  Based on a thorough examination of 30 studies from various academic databases, this systematic review investigates how exit exams affect curriculum design. To ensure methodological rigor, the review uses the PRISMA framework, which identifies important themes like curriculum alignment with exit exam requirements, the impact of high-stakes testing on instructional strategies, and the function of exit exams in quality assurance. Findings show that exit exams can influence curriculum changes, especially when it comes to matching academic material to professional competencies and industry standards. But there are drawbacks as well, like stress from tests, a focus shift in the curriculum, and disparities in student performance. The review emphasizes the necessity of a well-rounded curriculum that incorporates exit exam preparation with more general learning objectives. Future research directions and implications for educational practice are also covered. Findings reveal that exit exams can drive curriculum reforms, particularly in aligning educational content with industry standards and professional competencies. However, challenges such as exam-related stress, narrowing of curriculum focus, and inequities in student outcomes are also highlighted. The review underscores the need for balanced curriculum design that integrates exit exam preparation with broader educational goals. Implications for educational practice and future research directions are also discussed.